15N tracing studies including plant N uptake processes provide new insights on gross N transformations in soil-plant systems. (February 2020) - He, Xiaoxiang; Chi, Qiaodong; Cai, Zucong; Cheng, Yi; Zhang, Jinbo; Müller, Christoph
Abstract: Most soil N transformations studies are carried out using soil incubations without plants, despite the fact that plant-soil interactions potentially influence soil N dynamics. In this study, gross N transformation rates were quantified using a subtropical acidic forest with and without plants (and under different soil storage conditions). The results showed that the gross rates of N mineralization in air-dried and rewetted soil significantly increased, while the gross rates of nitrification and immobilization decreased, compared with fresh soil. Soil storage for more than one month at 4 °C (typical refrigerated conditions) and room temperature (25 °C) did not affect the gross rates of soil N mineralization and immobilization but significantly inhibited heterotrophic nitrification rates. Moreover, plants grown in the soil significantly stimulated gross rates of N mineralization, autotrophic and heterotrophic nitrification, and NO3 − immobilization. Plant NH4 + uptake rates (3.74 mg N kg −1 d −1 ) were 374 times greater than the NH4 + immobilization rate (0.01 mg N kg −1 d −1 ). The competition for NH4 + between plants and soil microorganisms led to strong feedback effects on soil N transformations. Based on our results we recommend to carry out 15 N tracing studies with plants to more realistically mimic field conditions. 15 N tracing techniques in combination with 15 N-tracing models, such as Ntrace Plant, provide a robust method to quantify soil N transformations and plant N uptake rates in plant-soil systems. Highlights: Gross rates of soil N transformations are significantly affected by plants. Strong feedback effects exist between soil N transformations and plants. The Ntrace Plant model can quantify soil N transformations in plant-soil systems.